An extremely rare complication of intestinal stoma formation: parastomal evisceration 1-year post-loop ileostomy. Issue 1 (19th January 2023) - Edwards Murphy, Amy; Stakelum, Aine; Razzak, Saad; Ashraf, Jawad; Awan, Faisal
Abstract: Intestinal stoma formation is an important and frequently performed procedure in emergency and elective general surgery. Parastomal evisceration is an extremely rare complication of stoma formation. The literature to date consists of a small number of case reports only. We report the case of a 54-year-old patient who presented 1-year post-loop ileostomy formation with a large parastomal evisceration. This was managed with emergency laparotomy. Our case highlights the high morbidity of this rare complication and the importance of emergent management and patient's education.